THE ENHANCEMENT OF SPEAKING SKILL THROUGHCLASSROOM PRESENTATION - Nian Masna Evawati; Murwani Ujihanti; Wasitoh Meirani (HOLISTICS, 2017)
The study was aimed to enhance speaking skill through classroom presentation. It tried to find the actual problems of speaking in the class and then solve them. The subjects of the research were the first semester students of Energy Engineering Study Program State Polytechnic of Sriwijaya. This study was qualitative research which was carried out using YouTube media and animation power point media. The research instruments for collecting data were observation sheets and rubric score of presentation. The data collection techniques were observing the classroom presentation activity done by the students and taking score using rubric during presentation. The data were analyzed in 3 stages: reducing the data, displaying the data and drawing conclusions. The results of the study showed that there were some enhancements in the students’ speaking skill. In using YouTube media, there were some unsuccessful actions. Meanwhile, in using animation power point media, the implementation of classroom presentation was successful in enhancing the students’ speaking skill.